Infrastructure Service Quality Analysis in Improving Public Trust in South Sorong District - Way, Alfius; Haning, Muh. Thahir; Ibrahim, Muh. Akmal (KnE Social Sciences, 2025)
Infrastructure services are the provision of services by the government to the community. The quality of infrastructure services in the region is one of the important aspects in sustainable development that is directly related to economic productivity in the region. Efficient infrastructure can strengthen regional competitiveness by attracting investment and opening up job opportunities. To ensure the sustainability of infrastructure services in the region, active community participation, cooperation between stakeholders, and policy support based on accurate data are needed. The quality of infrastructure services in a region not only supports economic activities but also functions as a primary tool to improve public accountability. Thus, efforts to improve the quality of infrastructure services must be the main focus in sustainable regional development planning. This type of research is a literature review through a meta-synthesis approach with the aim of deepening understanding of the phenomenon. Based on the results of the study, quality infrastructure services are key to supporting economic productivity, increasing regional competitiveness, and strengthening public accountability. Community participation, transparency of governance, and multi-party collaboration greatly influence the sustainability of infrastructure in encouraging public trust and improving service satisfaction. The public-private partnership model, with strengthening public trust and involvement, has proven effective in improving service quality. Therefore, sustainable regional development must prioritize the improvement of participatory and collaborative infrastructure services. Thus, it is concluded that sustainable regional development requires quality infrastructure, multi-party collaboration, active community participation, and data-based policies to increase public accountability.